(untitled) (Shaheed Smriti Journal, 2024)
This article examines the cultural significance and evolution of Tharu festivals, focusing on their role in preserving the community’s identity and heritage. The primary aim is to explore how these festivals reflect the spiritual beliefs, historical narratives, and social cohesion of the Tharu people, while also assessing the impact of modernization on their practices. Using interviews with community members and cultural analysis, the study highlights the challenges posed by urbanization, commercialization, and generational shifts. Key findings reveal a strong sense of cultural pride within the Tharu community, despite these pressures, and a growing effort to adapt the festivals while maintaining their authenticity. The article concludes by emphasizing the importance of proactive measures such as incorporating Tharu culture into educational curricula, fostering youth participation, and securing institutional support to safeguard these traditions. By balancing tradition with contemporary influences, Tharu festivals can continue to thrive, ensuring their cultural legacy endures for future generations.